2011
DOI: 10.1093/nar/gkr143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plastid psb T sense and antisense RNAs

Abstract: The plastid psbB operon is composed of the psbB, psbT, psbH, petB and petD genes. The psbN gene is located in the intergenic region between psbT and psbH on the opposite DNA strand. Transcription of psbN is under control of sigma factor 3 (SIG3) and psbN read-through transcription produces antisense RNA to psbT mRNA. To investigate on the question of whether psbT gene expression might be regulated by antisense RNA, we have characterized psbT sense and antisense RNAs. Mapping of 5′ and 3′-ends by circular RT–PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 27 publications
1
33
0
1
Order By: Relevance
“…To confirm the structure and composition of the poly(U) tracts, we carried out RT-PCR on circularized transcripts of psbA and psbC ( Fig. S2 and Dataset S1) (35,36). We found that the poly(U) tracts observed were generally between 15 and 30 nt in length, homopolymeric, and on the 3′ end of each transcript (as opposed to an internal insertion).…”
Section: mentioning
confidence: 92%
“…To confirm the structure and composition of the poly(U) tracts, we carried out RT-PCR on circularized transcripts of psbA and psbC ( Fig. S2 and Dataset S1) (35,36). We found that the poly(U) tracts observed were generally between 15 and 30 nt in length, homopolymeric, and on the 3′ end of each transcript (as opposed to an internal insertion).…”
Section: mentioning
confidence: 92%
“…Mechanistically, one could expect that enhanced antisense transcript accumulation interferes with translation efficiency of the corresponding sense transcript due to duplex formation, as it was suggested for the plastid psbT gene (Zghidi-Abouzid et al, 2011). This would provide a gene-group-specific mechanism that could prevent the formation of functional photosystem II and Cytb 6 f complexes.…”
Section: Impact Of Pap7-1 Deficiency On Plastid Gene Expressionmentioning
confidence: 96%
“…They focus on single RNAs and do not point to ncRNAs as a more general regulatory principle (Nishimura et al, 2004;Georg et al, 2010;Hotto et al, 2010;Zghidi-Abouzid et al, 2011). One study identified 12 ncRNAs in tobacco chloroplasts (Lung et al, 2006).…”
Section: Plastid Ncrnasmentioning
confidence: 99%
“…Cyanobacteria, the chloroplast progenitors, have a plethora of noncoding RNAs at their disposal to regulate gene expression . However, only a few potentially regulatory RNAs have been reported to be transcribed from plastid genes (Nishimura et al, 2004;Georg et al, 2010;Hotto et al, 2010;Zghidi-Abouzid et al, 2011). Therefore, chloroplasts may contain additional hitherto undetected genes for regulatory ncRNAs.…”
Section: Introductionmentioning
confidence: 99%